Russian grotesque realism : the great reforms and the gentry decline - Kokobobo, Ani (Columbus : The Ohio State University Press, 2018)
"A rereading of the Russian realist novel that proposes a hybrid genre, grotesque realism, to describe changes during the postreform era"--
The nihilist as grotesque other in Ivan Goncharov's The precipice and Nikolai Leskov's Cathedral folk -- Nihilist monsters and the failed gentry protagonist in Dostoevsky's Demons -- The gentry heroine as grotesque other: roots of Tolstoy's grotesque aesthetic in Anna Karenina -- Grotesque realism and the decline of the gentry in M. Saltykov-Shchedrin's The Golovlev Family -- The gentry milieu as grotesque microcosm in Tolstoy's Resurrection -- Rehabilitating all monsters: love and the rehumanization of the grotesque in the Brothers Karamazov -- Conclusion: The death of the novel.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Russian fiction -- 19th century -- History and criticism; Grotesque in literature; Realism in literature; Gentry in literature; Roman russe -- 19e siècle -- Histoire et critique; Grotesque dans la littérature.; Réalisme dans la littérature.; LITERARY CRITICISM -- Russian & Former Soviet Union; LITERARY CRITICISM -- General; Gentry in literature; Grotesque in literature; Realism in literature; Russian fiction; 1800-1899; Criticism, interpretation, etc